(untitled) (Abington, 2004)
This collection provides an authoritative review of the key issues in poultry processing. Part 1 discusses good practice during production, from breeding and husbandry to slaughter, secondary processing, packaging and storage. Part 2 analyses safety issues such as the control of microbial and chemical hazards, as well as how to maintain quality through the supply chain. CONTENTS Part 1 Processing: Breeding and quality; Husbandry techniques; Stunning and slaughter; Secondary processing; Processing of turkey, geese, ducks and game birds; Packaging. Part 2 Safety and quality: Shelf life and spoilage; Refrigeration; Other preservation techniques; Controlling microbial hazards; Chemical residues; Treatment and disposal of processing waste; Maintaining meat quality during processing; Measuring quality parameters; Managing safety and quality
Công nghệ chế biến thịt và gia cầm,Bảo quản và chế biến sản phẩm chăn nuôi,TT. Công nghệ thực phẩm (PTN)
Keywords: Poultry; Processing